China's Strategies in Economic Diplomacy: A Survey of Updated Lessons for Africa, the West and China - Simplice A. Asongu; Jacinta C. Nwachukwu; Gilbert A. A. Aminkeng (African Governance and Development Institute (AGDI), 2014)
The Washington consensus, the hitherto dominant scheme is being encroached by the Beijing model. Many African nations are increasingly embracing this Beijing approach because the dominant Western model has failed to deliver on a number of fronts. This is increasingly evident because China's economic diplomacy has been politely and strategically coined to achieve just that. A case study is used here to articulate the currents of the survey. The paper puts some structure on China's economic diplomatic strategies and discusses lessons for Africa, China and the West. It contributes to existing literature by critically engaging on why it is necessary for the West to adjust the conception and definition of the Washington Consensus as a complement to the Beijing model. In order to remain relevant in the 21st century and beyond, the Washington consensus can incorporate the Moyo (2013) conjecture which postulates that, while the Beijing model is optimal in the short-run, the Washington Consensus remains the optimal long-term development model because it is more inclusive.
Keywords: F19; F21; O10; O19; O55; 330; Economic relations; China; Africa